A comparative study of the occurence of anthracnose (Colletotrichum gloeosporioides) in cultivars of pepper (Piper nigrum L.) recently introduced in Porto Velho, state of Rondonia. - Rodrigues, João Elias L. F.; Lucchesi, Antonio A.; Viana, Francisco Marto P.; Albuquerque, Fernando C. de; Duarte, Maria de Lourdes R.; Medrado, Moacir José S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
In an experiment carried out in an experimental area of EMBRAPA (Brazilian Agriculture Research Enterprise) UEPAE (Unit for Execution of Research) of Porto Velho, State of Rondonia, Brazil, located at km 5.5 of the BR-364 Highway, latitude 8°46'5"S, longitude 63°5' Greenwich and altitude 96.3m above sea level, evaluations were made of both the occurence of anthracnose caused by the fungus (Colletotrichum goeosporioides) in 5 cultivars of pepper (Piper nigrum L.) at the time of the first yield, 18 months after planting and of the leaves, correlating them with productivity of the cultivars. The results obtained led to the following conclusions: the cultivar Guajarina showed to be less susceptible to anthracnose and more resistant to fall of the leaves; the cultivars Bragantina, Cingapura and Djambi behaved similarly as to fall of the leaves; the cultivars Bragantina and Cingapura had the same behavior and were less susceptible to anthracnose when compared with cultivars Djambi and Belantung, while the cultivars Belantung showed to be more susceptible to anthracnose and less resistant to fall of the leaves.